Temperature-dependent thermal properties of a paraffin phase change material embedded with herringbone style graphite nanofibers. (1st January 2015) - Warzoha, Ronald J.; Weigand, Rebecca M.; Fleischer, Amy S.
Highlights: The thermal properties of a PCM with nanofibers are determined. The solid-phase thermal conductivity scales exponentially with volume fraction. The liquid-phase thermal conductivity is only enhanced beyond a critical percolation threshold. The nanoscale interface resistance depends on the nanoparticle's dimensionality. The thermal diffusivity and volumetric heat capacity of the nanoenhanced PCMs are found. Abstract: In many studies, carbon nanoparticles with high values of thermal conductivity (10–3000 W/m K) have been embedded into phase change thermal energy storage materials (PCMs) in order to enhance their bulk thermal properties. While a great deal of work to date has focused on determining the effect of these nanoparticles on a PCM's solid phase thermal properties, little is known about their effect on its liquid phase thermal properties. Thus, in this study, the effect of implanting randomly oriented herringbone style graphite nanofibers (HGNF, average diameter = 100 nm, average length = 20 μm) on the bulk thermal properties of an organic paraffin PCM (IGI 1230A, T melt = 329.15 K) in both the solid and liquid phase is quantified. The bulk thermal conductivity, volumetric heat capacity and thermal diffusivity of HGNF/PCM nanocomposites are obtained as a function of temperature and HGNF volume loading level. It is found that the property enhancement varies significantly depending on the material phase. In order to explain the difference between solid and liquid phase thermal properties, heat flow at the nanoparticle–PCM and nanoparticle–nanoparticle interfaces is examined as a function of HGNF loading level and temperature. To do this, the solid and liquid phase thermal boundary resistances (TBRs) between the nanoparticles and the surrounding PCM and/or between contacting nanoparticles are found. Results suggest that the TBR at the HGNF–PCM interface is nearly double the TBR across the HGNF–HGNF interface in both solid and liquid phases. However, both the HGNF–PCM and HGNF–HGNF TBRs are at least an order of magnitude lower when the PCM is in its solid phase versus when the PCM is in its liquid phase. Finally, the effect of nanofiber concentration on the PCM's latent heat of fusion and melt temperature is investigated in order to determine the applicability of the HGNF/PCM nanocomposite in a wide variety of energy systems.